2013
DOI: 10.1088/1674-1056/22/5/055204
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of TiN/a-Si3N4thin film by using a Mather type dense plasma focus system

Abstract: A 2.3 kJ Mather type pulsed plasma focus device was used for the synthesis of a TiN/a-Si3N4 thin film at room temperature. The film was characterized using X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), and atomic force microscopy (AFM). The XRD pattern confirms the growth of polycrystalline TiN thin film. The XPS results indicate that the synthesized film is non-stoichiometric and contains titanium nitride, silicon nitride, and a phase of silicon oxy-nitri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The fundamental processes in the PF device during thin-film deposition are described as follows. 45 Collision of high-energy ions with the sample leads to cleaning, etching and abrupt heating of the Fig. 9 Current signal of a typical plasma focus discharge.…”
Section: Methodsmentioning
confidence: 99%
“…The fundamental processes in the PF device during thin-film deposition are described as follows. 45 Collision of high-energy ions with the sample leads to cleaning, etching and abrupt heating of the Fig. 9 Current signal of a typical plasma focus discharge.…”
Section: Methodsmentioning
confidence: 99%
“…[31] The main processes occurring in DPF during the sample processing are described as follows. [41] (i) Accelerated ions strike the sample resulting in high thermal gradients due to sufficient energy transfer. Consequently, abrupt heating followed by rapid cooling effects are 065204-2 generated in the sample surface.…”
Section: Experimental Setup and Methodsmentioning
confidence: 99%
“…It has been reported that the ion irradiation process in the plasma focus device is similar to transient thermal annealing and causes re-arrangement of atoms in the surface layer, resulting in the formation of nanoparticles. [41] As the bunching of nanoparticles is energetically favored, therefore it can be assumed that high surface energy and bond interactions among multiple phases of nanocomposite causes the gathering of primary nucleates into spherical agglomerates. [53] It can be seen that no such definite coagulation pattern is observed for the sample placed at 13 cm [Fig.…”
Section: Sem Analysismentioning
confidence: 99%
“…[15][16][17][18] The relativistic electrons are also used to ablate the material (placed at the anode tip) which reacts with the nitrogen plasma and to sputter the substrate material to form composite films. Films deposited by this device show superior surface qualities including good adhesion to the substrate surface and grain growth of different compounds through nucleation by successive focus shots at ambient temperature [19] and short nitriding time duration.…”
Section: Introductionmentioning
confidence: 99%